2016
DOI: 10.1210/en.2016-1342
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Involvement in Rat Amelogenesis: An Additional Way for Endocrine-Disrupting Chemicals to Affect Enamel Synthesis

Abstract: Endocrine-disrupting chemicals (EDCs) that interfere with the steroid axis can affect amelogenesis, leading to enamel hypomineralization similar to that of molar incisor hypomineralization, a recently described enamel disease. We investigated the sex steroid receptors that may mediate the effects of EDCs during rat amelogenesis. The expression of androgen receptor (AR), estrogen receptor (ER)-α, and progesterone receptor was dependent on the stage of ameloblast differentiation, whereas ERβ remained undetectabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 45 publications
2
30
0
1
Order By: Relevance
“…Concerning the AR, it has already been detected in dental pulp cells (Dale et al, 2002; Inaba et al, 2013). In addition, our past work, as well as the present study, show that AR expression in the maturation-stage ameloblasts which is higher than in the secretion-stage and mesenchymal cells, suggesting a selective role of androgens in enamel final mineralization (Jedeon et al, 2016b). Testosterone is able to modulate the expression of enamel key genes present in maturation-stage ameloblasts such as SLC26A4 (or pendrin) and KLK4 (Jedeon et al, 2016b).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Concerning the AR, it has already been detected in dental pulp cells (Dale et al, 2002; Inaba et al, 2013). In addition, our past work, as well as the present study, show that AR expression in the maturation-stage ameloblasts which is higher than in the secretion-stage and mesenchymal cells, suggesting a selective role of androgens in enamel final mineralization (Jedeon et al, 2016b). Testosterone is able to modulate the expression of enamel key genes present in maturation-stage ameloblasts such as SLC26A4 (or pendrin) and KLK4 (Jedeon et al, 2016b).…”
Section: Discussionsupporting
confidence: 76%
“…In addition, our past work, as well as the present study, show that AR expression in the maturation-stage ameloblasts which is higher than in the secretion-stage and mesenchymal cells, suggesting a selective role of androgens in enamel final mineralization (Jedeon et al, 2016b). Testosterone is able to modulate the expression of enamel key genes present in maturation-stage ameloblasts such as SLC26A4 (or pendrin) and KLK4 (Jedeon et al, 2016b). Moreover, the higher level of AR expression in dental epithelium than in testis suggests that ameloblasts are responsive to plasmatic testosterone and thus androgen regulation of final enamel mineralization.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Except PPARγ and ERβ, rodent ameloblasts express all these receptors and their expression levels vary depending on the ameloblast differentiation stage (Houari et al, 2016; Figure 1). Furthermore, we have shown that ERα is involved in pre-ameloblast proliferation (Jedeon et al, 2014b), and AR in the enamel terminal mineralization process (Jedeon et al, 2016b). Thus, mediated by these receptors, EDCs such as BPA and vinclozolin may disrupt amelogenesis.…”
Section: Evidencementioning
confidence: 99%
“…On the other hand, premature babies were reported to be contaminated with BPA and phthalates essentially due to medical devices (Calafat et al, 2009; Duty et al, 2013). And, both class of EDCs act via steroid receptors, ERs and AR, reported to modulate enamel key genes like KLK4 (Jedeon et al, 2016b). …”
Section: Evidencementioning
confidence: 99%